(untitled) (VERITAS LEGIS JOURNAL, 2026)
This article examines the optimal measures to ensure the proper conduct of a participant in criminal proceedings, such as a witness entitled to a defense, in the context of their purpose and legal status. The author constructively and critically analyzes a legislative proposal to amend Chapter 19 of the Criminal Procedure Code of the Republic of Kazakhstan (hereinafter referred to as the CPC RK) with a new measure of criminal procedural coercion, "Temporary Restriction on Leaving the Country," and strengthens the procedural liability of individuals with this status, along with suspects, accused, and defendants. The introduction of a travel ban for them, similar to the law for other defense representatives, outside the Republic of Kazakhstan is considered an unacceptable innovation that contradicts their status and unreasonably limits the personal freedom and immunity of witnesses entitled to a defense. The author of this article has developed a draft provision of the Criminal Procedure Code of the Republic of Kazakhstan that provides for the introduction of an additional travel ban exclusively for suspects, accused, and defendants when certain measures of criminal restraint (other than pretrial detention) are imposed on them.